Comparison of characteristics between scale model and CG for the experience by simple VR headset with the smartphone / Nozomi Ishiyama and Yuji Matsumoto - Ishiyama, Nozomi; Matsumoto, Yuji (2018)
The purpose of this study is to use a scale model, which has long been popular in the expression of architecture, for the simple VR headset using the smartphone (S-VR) which is popular nowadays. While investigating spatial reproducibility of the simulation using S-VR, which is one of the important tasks of utilizing VR technology in architecture field, we clarified the characteristics of the spatial impression which is felt by the difference between the scale model (Mod) and CG expressing VR space. We considered not only the merit of those, but also the characteristics. First of all, we compared S-VR and Liquid Crystal Display (LCD). We conducted an experiment by the Semantic Differential scale method (SD method), and subjects evaluated seven levels by the 13 selected adjective-pairs. S-VR gained a higher evaluation on the spatial reproducibility than LCD. Therefore, we continued the investigation focusing on S-VR. Next, we compared the impression of the space due to the difference in expression medium used in S-VR, that is, CG and Mod, and clarify their characteristics using analysis of variance. Mod tends to be evaluated as "Open", "Like", "Friendly", while CG did as "Luxury" or "Oppressed". In CG, the difference in patterns of space gave different impressions. However, in Mod, it was less likely to influence the impression, that is, whichever pattern was similar impression. As a result, when comparing impressions by Mod, it is necessary to pay attention to those characteristics. In addition to characteristics clarified in this research, considering physical conditions and the time to create Mod, for simulation comparing multiple patterns, it is best to use CG as a space expression medium. While, for instance presentation, in the case of expecting to give a better impression to the space, it is effective to use Mod.